2009
DOI: 10.1021/ja809637e
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Cross-Linking of an RNA Internal Loop by the Anticancer Drug Cisplatin

Abstract: Cisplatin is the most prominent member of a series of platinum(II) antitumor drugs that demonstrate activity based on binding to adjacent purines on genomic DNA. The interactions between cisplatin and alternate biomolecules, including chemically similar RNA, are less understood than are those for DNA. In order to investigate potential implications of platinum(II) drug binding to a structurally complex RNA, we have characterized the reaction between cisplatin and the internal loop of a 41-nucleotide subdomain d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 72 publications
3
53
0
Order By: Relevance
“…addition, cisplatin causes atypical cross-links in structurally complex RNAs, thereby preventing reverse transcription, indicating that the RNA binding may interfere with communicating sequence information (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…addition, cisplatin causes atypical cross-links in structurally complex RNAs, thereby preventing reverse transcription, indicating that the RNA binding may interfere with communicating sequence information (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…In the sections below the most recent advances in the elucidation of platinum-RNA interactions are summarized, mainly focusing on examples subsequent to the above-mentioned review [39]. In particular, the following aspects are covered: (i) RNA platination kinetics [45,70,[77][78][79] (Sections 3.1 and 3.2); (ii) some examples of platinum binding to structured RNAs [80], focusing on latest insights into platinum binding to ribosomal RNA [44,76,81] (Section 3.3); (iii) the effect of platination on RNA interference [82][83][84] (Section 3.4); (iv) the use of Pt-RNA adducts to study RNA structure and dynamics [85] (Section 3.5) and (v) recent methods to detect RNA-platinum adducts in cells [47,86,87] (Section 3.6).…”
Section: Platinum Binding To Rnamentioning
confidence: 99%
“…This finding suggests that short RNAs may also represent good targets for cisplatin [77,78], and prompted further studies to better elucidate the basis of platinum-RNA interaction. Interestingly, in vitro studies performed using mono-aquated platinum complexes have shown that RNA platination kinetically competes or is even preferred over DNA platination [80,93]. Elmroth and co-workers investigated the interaction of cisplatin with the full length tRNA Ala and a short hairpin model (Mh Ala ) of its GC rich acceptor stem region ( Fig.…”
Section: Platinum Binding To Rnamentioning
confidence: 99%
See 2 more Smart Citations